Leadership Configurations Supporting TOGAF-Based Information System Architecture at Jenderal Achmad Yani University - Sigit Anggoro; Asher Nuche (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2025)
Digital transformation in higher education institutions demands integration between information technology, organizational culture, and adaptive leadership. This study aims to analyze the configuration of leadership styles in supporting The Open Group Architecture Framework (TOGAF) based information system architecture at Jenderal Achmad Yani University (UNJANI), a tertiary institution under the TNI Army Foundation which is building a transformation towards a Smart Military University. This research uses a qualitative approach with a case study method, relying on data from in depth interviews, participant observation and institutional documentation. The research results show that the success of digital transformation in UNJANI is supported by a combination of four leadership styles: military leadership (emphasizing discipline and command), transformational leadership (focusing on vision and empowerment), distributed leadership (emphasizing collaboration and collective decisions), and e-leadership (utilization of information technology in leadership). These four styles play a role in various phases of TOGAF, especially in Architecture Vision, Business Architecture, and Implementation Governance. This study shows that contextual, flexible, and values based leadership is a key factor in the success of information systems architecture in higher education environments.